Synthesis of surface-active N-heterocyclic carbene ligand and its Pd-catalyzed aqueous Mizoroki–Heck reaction. Issue 27 (7th July 2016) - Taira, Toshiaki; Yanagimoto, Takaya; Sakai, Kenichi; Sakai, Hideki; Endo, Akira; Imura, Tomohiro
Abstract: A surface-active N -heterocyclic carbene (NHC) ligand with an octaethylene glycol monomethyl ether and n -dodecyl chain was synthesized. The NHC and its Pd complex behaved as a general surfactant, and hydrophobic oily substrates such as iodobenzene and styrene were emulsified in water, resulting in the acceleration of the Mizoroki–Heck reaction under heterogeneous conditions. Our results demonstrated that the reactive emulsion interface rendered by the surface-active NHC is effective for the aqueous Mizoroki–Heck reaction. Graphical abstract: